2003
DOI: 10.1159/000070477
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Monocytes Enhances IL-5 Gene Transcription in Peripheral T Cells of Asthmatic Patients

Abstract: Background: The regulatory mechanisms of IL-5 gene transcription in human peripheral T cells are unclear because the transfection efficiency of plasmid constructs into nontransformed T cells is very low. Methods: Concanavalin A (ConA)-stimulated blastocytes derived from peripheral blood lymphocytes of asthmatic subjects were transiently transfected with the human IL-5 gene promoter/enhancer-luciferase gene construct, pIL-5 (–511)Luc, and cultured with THP-1 cells (human monocytoid cells) and anti-CD3 monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The importance of the Ets1 site and the synergistic interactions with GATA-3 and AP-1 were also demonstrated for the first time with freshly prepared normal human T cells. Our use of a high efficiency transfection method allowed these studies to be done with primary T cells from healthy donors rather than needing to use T cells from asthma patients (25,26). Taken together our findings suggest that Ets1, AP-1 and GATA-3 may be part of a higher order transcriptional complex involved in regulating human IL-5 expression in T cells.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The importance of the Ets1 site and the synergistic interactions with GATA-3 and AP-1 were also demonstrated for the first time with freshly prepared normal human T cells. Our use of a high efficiency transfection method allowed these studies to be done with primary T cells from healthy donors rather than needing to use T cells from asthma patients (25,26). Taken together our findings suggest that Ets1, AP-1 and GATA-3 may be part of a higher order transcriptional complex involved in regulating human IL-5 expression in T cells.…”
Section: Discussionmentioning
confidence: 77%
“…Earlier work with T lymphocytes from asthmatic patients (25,26) showed a role for the proximal promoter region in regulating IL-5 transcription but no detailed studies were carried out. We have used HSB-2 cells to look in detail at the role of three putative sites in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted previously, the fact that BALF TGF-β levels decreased upon monocyte depletion in parallel with those of all other measured cytokines argues against the importance of TGF-β as an inhibitory factor in our asthma model. A pathogenic role of monocytes might be explained by previous observations identifying circulating monocytes from asthmatics as a source of IL-5 [46–48], which is an eosinophil chemoattractant. Finally although our data fail to support that circulating monocytes serve as precursors for AMs, previous studies have shown that blood monocytes can be precursors for lung dendritic cells in both steady-state conditions [49] and in models of allergic asthma [50] and infectious lung disease [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…THP-1 cells secrete T cell recruiting and differentiating cytokines, such as IL-6 and IL-8 [56], leading to moderate stimulation of T cells [57,58]. HL-60 cells produce IL-6 [59] and IL-8 [60] and can also stimulate T cells upon activation, albeit moderately [61,62].…”
Section: Antigen Up-take and Presentationmentioning
confidence: 99%